Digital Media in TEFL: Lecturer’s Perceptions at an Islamic Institute in Jambi - Permana, Arya Geni; Erniyati, Yelni (Universitas Islam Negeri Palopo, 2025)
This study investigates an English lecturer’s perceptions of digital media integration in Teaching English as a Foreign Language (TEFL) at a rural Islamic institute in Jambi, Indonesia. Using a qualitative single-case study design, data were collected through semi-structured interviews with one lecturer at Institut Agama Islam Negeri Kerinci. Thematic analysis revealed six key themes: digital media is perceived as beneficial for increasing student engagement, tools are selected strategically based on language skills, and digital integration is hindered by limited infrastructure and institutional support. Despite these barriers, the lecturer demonstrated strong professional agency by using offline alternatives, engaging in training, and adapting technology to student needs. Platforms such as YouTube, Google Classroom, and Quizizz were commonly used to support listening, grammar, and classroom management. While digital tools enhanced learner autonomy and motivation, challenges remained in curriculum flexibility and equitable access. Digital integration success in TEFL not only requires good infrastructure but also institutional support and empowering the lecturer. In brief, this study offers valuable insights for future research to examine how digital media are utilized in TEFL classes, especially in rural areas.